Populism and Globalization - Mansbach, Richard W. author. aut Link
XIV, 529 p. 1 illus.
Keywords: This book describes the global spread of nationalist-populism by rightwing and racist political parties; their impact on political, economic, and sociocultural globalization; and the corrosive impact of this ideology on the global liberal order that emerged after World War II under United States leadership. The global liberal order is a system of norms including peace and security, democracy, human rights, free trade, financial stability and support for a broad range of international governmental organizations and treaties fostering interstate and transnational cooperation to advance those norms and resolve collective problems. Examples of these organizations are the United Nations, European Union, NATO, World Health Organization, World Trade Organization, World Bank, International Monetary Fund, and the Paris Climate Accord. Suitable for interested scholars and general readers as well as a classroom text. Yale H. Ferguson is Emeritus Distinguished Professor of Global and International Affairs, Rutgers University. He was Co-Director and remains a Professorial Fellow at the graduate Division of Global Affairs at Rutgers-Newark. He is an elected Member of the European Academy of Arts and Sciences and has been a Visiting Fellow at the University of Cambridge, the Norwegian Nobel Institute, and the University of Padova, as well as Fulbright and Honorary Professor at the University of Salzburg. Richard W. Mansbach is Professor of Political Science at Iowa State University. He formerly served as Chair of the Department of Political Science at Iowa State and at Rutgers University-New Brunswick. He was a Marshall Scholar at Oxford University and three times a Fulbright Professor, in Singapore, Seoul, and Vienna. He and Ferguson both received a Distinguished Scholar Award from the Historical International Relations Section of the International Studies Association in 2017. Ferguson and Mansbach have previously co-authored: Globalization: The Return of Borders to a Borderless World?; A World of Polities: Essays in Global Politics; Remapping Global Politics: History’s Revenge and Future Shock; The Elusive Quest Continues: Theory and Global Politics; Polities: Authority, Identities, and Change; The State, Conceptual Chaos, and the Future of International Relations Theory; The Elusive Quest: Theory and International Politics; and The Web of World Politics: Nonstate Actors in the Global System.